Chapter Trent’anni di linguistica slava in Italia - COTTA RAMUSINO, PAOLA MARIA (Firenze University Press, 2025)
The article offers an overview of the scholarly publications by Italian Slavists that appeared during the period 1991-2021 on to the subject of Slavic linguistics